2019
DOI: 10.37265/japiv.v11i1.5
|View full text |Cite
|
Sign up to set email alerts
|

A Structured Approach for Questionnaire Survey of Construction Delay

Abstract: Construction delay is a common problem costing the industry billions of dollars every year. The first step to reduce this unnecessary loss is to identify the major delay factors. More than 200 studies on major construction delays have been reported using self-administered questionnaire surveys of views of project participants. The present approach adopted is reviewed by a case study of Egypt. Thirty-two delay factors were identified as major construction delay factors. A thorough review of these eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The Cronbach's Alpha Coefficients of the internal consistency reliability tests for risk factors' frequency and severity ratings of the survey results are 0.928 and 0.942 respectively. Litwin & Fink (1995) and Kog (2019) suggested that consistency is high when Cronbach's alpha is above 0.7. This confirmed that there is high internal consistency among the answers.…”
Section: Discussionmentioning
confidence: 99%
“…The Cronbach's Alpha Coefficients of the internal consistency reliability tests for risk factors' frequency and severity ratings of the survey results are 0.928 and 0.942 respectively. Litwin & Fink (1995) and Kog (2019) suggested that consistency is high when Cronbach's alpha is above 0.7. This confirmed that there is high internal consistency among the answers.…”
Section: Discussionmentioning
confidence: 99%
“…A number of 200 questionnaires were distributed via an online survey (Google Docs) to respondents (project manager with prior expertise in managing sustainable construction), and 153 responses were successfully received, resulting in a response rate of 76.5%. A response rate minimum of 50% is considered realistic (Kog, 2019). In light of these points, the response rate can be regarded as capable of producing reliable results.…”
Section: 30 Methodologymentioning
confidence: 99%